Which Antimicrobial Agent is Likely to be the Best for Treating Clostridium difficile Infections? A Bayesian Network Meta-Analysis of Randomized Clinical Trials - Sridharan, Kannan; Sivaramakrishnan, Gowri (Drug Research, 2019)
Background Vancomycin, metronidazole, fidaxomicin, teicoplanin, fusidic acid and bacitracin have been recommended for the treatment of Clostridium difficile infections (CDI). We conducted a Bayesian network meta-analysis comparing all the antimicrobial agents used in CDI.Methods Electronic databases were searched for randomized controlled trials comparing antimicrobial agents used for CDI. Risk of bias was assessed. Random effects model was used to derive the mixed treatment comparison estimates. Odds ratio with 95% confidence intervals was used as effect estimate.Results Seventeen studies were included in this meta-analysis. Teicoplanin was observed to perform better than vancomycin, metronidazole, fusidic acid and bacitracin to achieve the symptomatic cure. Teicoplanin was also associated with higher rates of bacteriological cure than vancomycin and metronidazole. Fidaxomicin is associated with significantly higher rates of symptomatic cure than vancomycin, bacitracin and metronidazole and is similar to teicoplanin.Conclusion To conclude, teicoplanin and fidaxomicin have been observed to perform better than other antimicrobials for the treatment of CDI. We recommend conducting high quality randomized controlled clinical trials evaluating teicoplanin and fidaxomicin with other standard interventions for the management of CDI.
Keywords: Teicoplanin; Vancomycin; Metronidazole; Bacitracin